Anti-globulin responses to rat and humanized CAMPATH-1 monoclonal antibody used to treat transplant rejection. - Rebello, P; Hale, G; Friend, P; Cobbold, S; Waldmann, H (1999)
BACKGROUND: Antiglobulin responses are a significant limitation to the repeated use of murine monoclonal antibodies for treatment of transplant rejection. It is hoped that these might be largely overcome by using antibodies genetically engineered to resemble human antibodies. METHODS: We have compared the responses in patients treated with the CD52 monoclonal antibodies CAMPATH-1G (rat IgG2b) or its humanized derivative, CAMPATH-1H (human immunoglobulin G1). RESULTS: A majority of patients (15 of 17) made responses to the rat antibody, but there were no detectable responses to the humanized antibody (0 of 12). CONCLUSIONS: Although anti-idiotype responses are theoretically possible against humanized therapeutic antibodies and are especially likely to be provoked by cell-binding antibodies, these data show that humanization offers a significant reduction in immunogenicity, potentially allowing repeat courses of treatment.